Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

UV-B protective potential and flavonoid content of leaf hairs of Quercus ilex - Skaltsa, Helen; Verykokidou, Evmorphia; Harvala, Catherine; Karabourniotis, George; Manetasi, Yiannis (Phytochemistry, 1994)
Flavonoids of non-glandular leaf hairs from Quercus ilex were analysed. The main compounds were acylated kaempferol glycosides. Acylation shifted the absorption peak into the ultraviolet-B region of the spectrum in which intact trichome layers absorbed strongly. Ultraviolet-B radiation caused a considerable reduction of photosystem II photochemical efficiency only in dehaired leaves. It is suggested that leaf hairs, besides other roles, may function as an effective filter against the harmful ultraviolet-B radiation.
Keywords: Fagaceae; flavonoids; Holly Oak; leaf hairs; Quercus ilex; UV-B damage